Documentation et conservation-restauration d’un autel bouddhique en bois laqué et doré, provenant du Japon - Violaine Brard (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
A small gilded and lacquered wooden Buddhist altar has been  kept for years in a cardboard box in the storage rooms of the Georges Labit museum in Toulouse. The challenge of this project  was to collect information on the origins of the altar, its time of creation and its specific function  in the  country of origin. The research focused on raising understanding  how this object has been transferred from  the Japanese culture  into a French collection that has been developed by Georges Labit a traveller and collector of the late nineteenth century. Examinations  showed that the altar with its original Japanese wooden support and polychromy showes over paints that have been applied in Europe  during the nineteenth century. These over paints demonstrate its laborious (?) passage from one country to another. Obviously, the new owners of the altar  intervened by repairing damages caused during  the journey of the artefact and by adapting the appearance  to Western aesthetic standards.